Involvement of Islamic attributes in Shariah-compliant hospitality: a study on Muslim students in Malaysia - Haque, A. K. M. Ahasanul; Ahmed, Faruk; Rashel, Abu; Abdul Razak, Dzuljastri (2017)
Introduction: Both Muslim Ummah and their Shariah-based demand are constantly growing and consolidating mostly in the Asia continent, and more or less in other continents around the globe. Paralleled with its growth, challenges to manage the gap between Shariah-compliant tourism and contemporary tourism are getting complicated. So, study on Shariah-compliant tourism is the solution for the smooth and sustainable growth of this industry. Methodology: At the stance of positivism, the values of some selected Islamic attributes of hospitality were entrenched to investigate whether they play a role behind Shariah-compliant hospitality intention through mediating Shariah-compliant attitude in the hotel industry of Malaysia. From the campus premises, 102 Muslim students were conveniently chosen and surveyed based on a self-administered questionnaire. Findings: From the Structural Equation Modelling (SEM) approach, it was uncovered that the Shariah-compliant hospitality attributes significantly drove the Shariah-compliant attitude, and Shariahcompliant attitude significantly affected Shariah-compliant intention. Contribution: The empirical study, holding this idea apart from others’ contributions to Shariah-compliant hotel service field, was conducted from Malaysia perspective for the first time. Both Muslim Ummah and their Sharia-based demand are constantly growing and consolidating mostly in the Asia continent, and more or less in other continents around the globe. Paralleled with its growth, challenges to manage the gap between Shariah-compliant tourism and contemporary tourism are getting complicated. Implications consistent with them have been approached for attaining sustainable development of the Islamic tourism market in the Islamic world, especially in the country with a scenario like Malaysia.